Association of Irisin Serum Concentration and Muscle Strength in Normal-Weight and Overweight Young Women - Martínez Muñoz, Ilse Yessabel; Camarillo Romero, Eneida del Socorro; Correa Padilla, Trinidad; Santillán Benítez, Jonnathan Guadalupe; Camarillo Romero, María del Socorro; Montenegro Morales, Laura Patricia; Bravo, Gabriel Gerardo Huitrón; Garduño García, José de Jesús (Frontiers in Endocrinology, 2019)
Background: Irisin is a muscle-contraction-induced myokine. In previous studies, it has been related to exercise type, fitness and physical activity; however, evidence is not consistent. Thus, the aim of this study was to research the association between health-related fitness and irisin in young women. Methods: The study was designed as a prospective cross-sectional one. Young, healthy, nonsmoking women were enlisted. The sample comprised 40 overweight (OW) and 40 normal-weight (NW) individuals. The average age was 18.63 ± 0.63 and 18.78 ± 0.73 years, respectively. Components of health-related fitness, metabolic parameters, serum irisin and body composition were analyzed. Results: Statistically significant differences were found in physical tests between NW and OW groups for one-leg standing, hand grip strength, vertical jump, modified push-up, fitness index and maximal oxygen uptake (VO2MAX). There were no differences in concentrations of serum irisin between the groups. We found a positive correlation between irisin and hand grip strength (r = 0.374, p = 0.023). In a multivariate analysis adjusted by body fat, a significant association between irisin and hand grip strength was observed in OW group (β = 0.380, p = 0.026); as well, a positive association between irisin and one-leg standing test in NW group (β = 0.311, p = 0.044) was found. Conclusions: According to our findings, hand grip strength could be linked to irisin concentration in overweight young women.